Community Perception and Service Utilization of Diabetic Retinopathy Management Project in Gaddap Town - Muhammad Faisal Fahim, Muhammad Saleh Memon, Seema N. Mumtaz, Sikandar Ali Sheikh (Pakistan Journal of Ophthalmology, 2016)
Purpose: To find the changes in the community perception and service utilization of diabetic retinopathy management project in Gaddap Town. Study Design: Cross sectional study. Place and Duration of Study: The first phase of the project covered Jannuary 2006 to December 2008, second from Jannuary 2009 to Dec. 2011 and final from Jan 2012 to March 2015 in Gaddap town. Material and Methods: A community based project was initiated by Al-Ibrahim Eye Hospital Karachi to devlop a replicable model for prevention and control of diabetic retinopathy in Gaddap town. All individuals in the age group 30 years were included except those with history of any addiction or any chronic disease. Post prandil (2.5 hours after breakfast) blood sugar levels was checked with Glucometer. Blood glucose level of 140 mg/dl was considered non diabetic, 199 mg/dl was considered latent diabetes and 200 mg/dl was considered as diabetes. Diabetics were screened for retinopathy. Diabetics with retinopathy were referred to tertiary center for management. Results: Blood screening was availed by 42,998 persons with combined mean age of 36.26 ± 9.8. During three phases response to blood screening was 23%, 14.1%, 13.8% and to retinal screening was 26.57%, 55.6%, 81.1%. Turn out at tertiary center was 18.1%, 24%, 42.2%. Acceptance of Laser therapy was 17.3%, 83.3%, 68.4%. Conclusion: Service utilization is a challenge; but it can be improved with persistant awareness, councilling, quality and patient friendly service. Key words: Service acceptance, Diabetic retinopathy; Diabetic Screening.